2018
DOI: 10.1177/0963721418760214
|View full text |Cite
|
Sign up to set email alerts
|

Moving Beyond a One-Size-Fits-All View of Positive Affect in Health Research

Abstract: Although the literature that connects positive affect (PA) to health has exploded over the last 20 years, the approach to studying this topic has remained simplistic. Specifically, researchers overwhelmingly rely on the principle that all PA is healthful, all of the time. Here, we review recent studies indicating that a more nuanced approach is valuable. In particular, we demonstrate that a more thoughtful approach to factors such as arousal, culture, timing, and measurement type results in a more complex pict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 44 publications
2
31
0
Order By: Relevance
“…These somewhat paradoxical findings may be explained by the notion that emotional states high in arousal—regardless of positive or negative valence—may be more strongly associated with cardiovascular risk factors. In fact, the majority of questionnaires that assess positive emotionality focus on the experience of positive emotions that are high in arousal (e.g., excitement, joy, and elation) rather than low arousal states (e.g., contentment, calm, relaxed; Pressman & Cross, 2018), including the three questionnaires used in the current study. As such, future studies should assess the range of trait emotionality at all points along the arousal—valence continuum to gain a more nuanced understanding of how emotions and the components of emotional experiences, valence and arousal, might influence cardiovascular disease risk.…”
Section: Discussionmentioning
confidence: 99%
“…These somewhat paradoxical findings may be explained by the notion that emotional states high in arousal—regardless of positive or negative valence—may be more strongly associated with cardiovascular risk factors. In fact, the majority of questionnaires that assess positive emotionality focus on the experience of positive emotions that are high in arousal (e.g., excitement, joy, and elation) rather than low arousal states (e.g., contentment, calm, relaxed; Pressman & Cross, 2018), including the three questionnaires used in the current study. As such, future studies should assess the range of trait emotionality at all points along the arousal—valence continuum to gain a more nuanced understanding of how emotions and the components of emotional experiences, valence and arousal, might influence cardiovascular disease risk.…”
Section: Discussionmentioning
confidence: 99%
“…Using various forms of operationalization, several studies report associations of positive affect with a wealth of positive outcomes. For example, positive affect is positively associated with meaning in life [3], future life satisfaction [4], positive health behaviors [5], restful sleep [6], and longevity [7]; for reviews, see [8,9]; and [10]; see [5] as well as [11] for more nuanced approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Positive affect refers to the subjective experience of pleasant affective states, such as enthusiasm or joy, over shorter and longer time intervals (Pressman & Cross, 2018; Watson, Wiese, Vaidya, & Tellegen, 1999). It is conceptually and empirically distinct from negative affect (Watson et al, 1999) and other aspects of well-being (e.g., life satisfaction; Diener, 2000).…”
Section: Pathways From Positive Affect To Memorymentioning
confidence: 99%
“…However, other longitudinal studies have found no associations between positive affect and memory decline (Berk, van Boxtel, Köhler, & van Os, 2017; Brailean et al, 2016). These studies provide important insights, but they have not always used gold-standard measures of positive affect (Pressman & Cross, 2018), objective measures of memory functioning, or sample sizes that afforded sufficient statistical power to detect small effects.…”
Section: Pathways From Positive Affect To Memorymentioning
confidence: 99%